Emotional Intelligence (EI) among Bank Employees: An Empirical Study - Sahi , Anu; Pahuja, Anurag (Gyan Management Journal, 2012)
The rules of work are changing increasingly. The increasing complexities both in business as well as in uman behavior have created the need for not only people with high Intelligent Quotient (IQ) but people with high Emotional Quotient (EQ) also. In the present era where the slogan "Customer is the ing" prevails in every organization, and the emotionally imbalanced employees may find it hard to chi eve their targets or deliver their reports on time. The way a person feels affects the way he behaves 'Id the way he behaves will not only have the relationship with his achievements, but also affects the rformance of those around him. Keeping this in view, the present paper is an attempt to unveil the ception of bank employees towards emotional quotient, and finding the factors affecting their otional intelligence and itse_ffecton their performance.
Keywords: Intelligent Quotient; Emotional Quotient (EQ); Performance; perception